Pengetahuan Remaja Putri Tentang Kesehatan Reproduksi dan Manajemen Prakonsepsi - Diva Maulida Gunawati; Sri Wahyuni; Apriliani Yulianti Wuriningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Knowledge of the reproductive system and organs greatly affects the health of adolescent girls. Adolescence is also called puberty. Preconception is the time when the egg unites with the sperm, which occurs in women before pregnancy. Methods: This study is a non-experimental study that applies a quantitative approach, where the information collected is in the form of numbers. It implements a descriptive analytic design with a cross-sectional correlational method. Data was collected by filling out a questionnaire. The number of respondents was 107 people who were taken by purposive sampling technique. The data obtained were then statistically analyzed using Somers'd Correlation. Results: The results obtained from the analysis showed that of the 107 respondents, most had characteristics of 17 years of age as much as 72.9%. The results also showed that 82.2% of respondents experienced good reproductive health knowledge and 3.7% of respondents experienced poor reproductive health knowledge. A total of 51.4% of respondents had good preconception management and 2.8% of respondents had poor preconception management. Conclusion: In this conclusion states that, there is a relationship between the knowledge of adolescent girls about reproductive health and preconception management with a value (p value = 0.001 <0.05) and the value of r (correlation) is 0.627 which indicates that the value of a strong correlation means, the better the reproductive health knowledge, the better the preconception management value.